Digital subtraction angiography (DSA) is superior to duplex ultrasound in diagnosis of extracranial carotid stenosis - a comparative study - Dey, Subash Kanti; Bakshi, Lipy; Shahidullah, Md; Habib, Ahsan; Battacharya, Manabendra; Rizvi, Abu Nasar; Anwarullah, AKM (Bangladesh Medical Journal, 2014)
Digital subtraction angiography (DSA) is the gold standard investigation to assess the extracranial stenosis of carotid vessels. But this is an invasive diagnostic tool. So it is still a controversial issue whether duplex ultrasound is an alternative to DSA for measurement of stenosis of carotid vessels. This prospective crossectional observational study was conducted in the department of Neurology, BSMMU, Dhaka from May 2012 to April 2013 to assess the diagnostic accuracy of duplex ultrasound and its potential to replace DSA before performing carotid endarterectomy (CEA) and carotid stenting. Total of 38 patients, 33 patients of nondisabling ischaemic stroke and 5 patients with history of TIAs whose extracranial carotid stenosis was >50% on duplex ultrasound were selected for DSA. DSA was done on these vessels and stenosis was measured using NASCET criteria. Results of USD and DSA were compared to determine the sensitivity, specificity and accuracy of duplex ultrasound (USD). At 70% stenosis of right internal carotid artery and left internal carotid artery the sensitivity, specificity and accuracy were 93.8%, 63.7%, 89.5% and 93.3%, 75%, 89.5% respectively. This level of diagnostic efficiency of USD is less than that of DSA of carotid arteries. It was found in this study that, USD underestimates or overestimates the degree of carotid stenosis. DSA was safe and effective in determining stenosis in this study & there was no 67 complication. So before taking any decision for carotid endarterectomy or carotid artery stenting, digital subtraction angiography of carotid vessels should be done. DOI: http://dx.doi.org/10.3329/bmj.v43i2.21385 Bangladesh Med J. 2014 May; 43 (2): 67-71